Are ecosystem service hotspots located in protected areas? Results from a study in Southern Italy. Issue 73 (July 2017) - Spanò, Marinella; Leronni, Vincenzo; Lafortezza, Raffaele; Gentile, Francesco
Highlights: An agroforestry landscape is analyzed in terms of ecosystem services (ESS) supply. A replicable approach was applied to assess ESS and their trade-offs. Results reveal that ESS supply varies greatly with distinct spatial distributions. Findings show that natural protected areas include a significant percentage of ESS hotspots. This approach detects areas of high ESS supply for sustainable resource management. Abstract: Ecosystems are essential in providing multiple services to society. However, understanding ecosystem services (ESS) in terms of spatial distribution and trade-offs still remains a challenge for landscape planners and natural resource managers. In this paper, we analyzed the supply of a set of ESS – carbon storage, soil erosion protection, biodiversity, and recreation – within the landscape surrounding the city of Bari in Southern Italy. Through an analysis of this landscape, which includes natural protected areas, such as Natura 2000 Network sites, national and regional parks and nature reserves, and in view of the recent Fitness Check of the Nature Directives, we aimed to provide answers to the following questions: (i) Where are the areas of high and low supply of individual ecosystem services located?; (ii) Where do ecosystem service trade-offs (i.e., 'hotspots' and 'coldspots') occur? ; and (iii) To what extent are ecosystem service hotspots and coldspots located within or outside of natural protected areas? Results show that most of the landscape in the study area supplied at least one of the selected ESS and that ESS hotspots were mostly located within forested and/or natural areas. Hotspots occupied 8.0% of the total landscape, with 23.7% located in natural protected areas. Coldspots were scarce and equal to 2.4%; they constituted only 0.1% of natural protected areas. Almost all of the landscape (89.6%) consists of intermediate areas (i.e., between hotspots and coldspots); 76.2% of natural protected areas consists of intermediate areas. This latter finding is relevant because the high intermediate classes are potentially high-performing areas, which lie mainly on the borders of protected spaces; they can positively influence ecological processes and thus enhance a wide-ranging provision of ESS. Our results highlight the importance of analyzing landscapes to facilitate the selection of priority areas where management efforts would yield maximum benefits.